Origin of prehistoric cattle excavated from four archaeological sites in central and northeastern Thailand. (19th May 2019) - Siripan, Sirianong; Wonnapinij, Passorn; Auetrakulvit, Prasit; Wangthongchaicharoen, Naruphol; Surat, Wunrada
Abstract: Cattle have been domesticated in Southeast Asia, including Thailand, for thousands of years, but the history of cattle domestication in the region remains unclear. To date, only genetic studies of modern Thai cattle DNA have been reported. To gain some insight into cattle domestication in the country, a total of 56 cattle remains excavated from four archaeological sites (dated to between 3550 and 1700 years before present (YBP)) in northeastern and central Thailand were analysed in this study. Of 56, the 157-bp D-loop fragment was successfully generated from 26 samples, all of which belonged to Bos taurus in haplogroup T/T3. One haplotype contained 19 members from all four archaeological sites and clustered with the ancient B. taurus from Iran, Turkey and China. Other haplotypes have not shared haplotype with B. taurus from other countries but they showed close relationship to those from China. This represents the first genetic evidence that B. taurus was domesticated in Thailand between 3550 and 1700 YBP. In addition, the close relationship among ancient Thai, Iranian and Chinese taurines suggests that cattle from the Near East were introduced into North China, and were subsequently brought into Thailand thousands of years ago.